CDKN2A Deletion in Melanoma Excludes T Cell Infiltration by Repressing Chemokine Expression in a Cell Cycle-Dependent Manner - Zhu, Zhen; Song, Hao; Xu, Juan (Frontiers in Oncology, 2021)
T-cell-mediated immune response is the prerequisite for T-cell-based immunotherapy. However, the limitation of T-cell infiltration in solid tumors restricted the therapeutic effect of T-cell-based immunotherapy. The present study screened the molecular and genetic features of The Cancer Genome Atlas (TCGA)-skin cutaneous melanoma (SKCM) cohort, revealing that T-cell infiltration negatively correlated with genome copy number alteration. The analysis of the TCGA-SKCM cohort indicated that the copy number of CDKN2A was significantly decreased in patients with low T-cell infiltration. The results were validated in the other two melanoma cohorts (DFCI, Science 2015, and TGEN, Genome Res 2017). Besides, the immunohistochemistry analysis of CDKN2A and CD8 expression in 5 in situ melanoma and 15 invasive melanoma patients also showed that CD8 expression was decreased in the patients with low CDKN2A expression and there was a positive correlation between CDKN2A and CD8 expression in these patients. Interestingly, the CDKN2A deletion group and the group with low expression of T-cell markers shared similar gene and pathway alteration as compared with the normal CDKN2A group and the group with high expression of T-cell markers, especially the chemokine pathway. Further mechanistic study indicated that CDKN2A enhanced T cell recruitment and chemokine expression possibly through modulating MAPK and NF-κB signaling pathways in a cell cycle–dependent manner. Finally, we also found that CDKN2A deletion negatively correlated with the expression of T-cell markers in many other cancer types. In conclusion, CDKN2A deletion could inhibit T cell infiltration by inhibiting chemokine expression in a cell cycle dependent manner.